Adapting Piagetian Concepts to L2 Learning: Pedagogical Implications - BOULKROUN , Fouad (Journal of Human Sciences, 2020)
Piaget believed that action stands at the very heart of any intellectual development. In a similar fashion, the author is inclined to argue that success in L2 learning takes its roots in action. The aim is to call for adapting Piagetian concepts to L2 learning. In the present study, the author will attempt to: (1) account for some of Piaget’s basic concepts within the context of general learning, namely action, adaptation (through the interplay of the two processes of assimilation and accommodation), and equilibration, (2) show how these may be used in the area of language learning and communication, (3) show how affective influences have some bearing on action, and (4) suggest and discuss some pedagogical implications with respect to interest, personality, learning style, streaming, and learning strategies along with their teachability.